Effect of Actinomycin D on the Transfer of Ribonucleic Acid from Nucleus to Cytoplasm in Lactobacillus acidophilus - Chai, Ning-Chun (1970)
After starvation for deoxyribosides, the deoxyribonucleic acid (DNA) of Lactobacillus acidophilus is restricted to a localized region of the cell. (3)H-uracil is first incorporated into such a restricted region but subsequently is found throughout the cell. This spread occurs despite the absence of protein synthesis and a major reduction in the rate of ribonucleic acid (RNA) synthesis. However, blocking RNA synthesis with actinomycin D restricts incorporation to a localized region of the cell. It is concluded that uracil is first incorporated into RNA in the bacterial nucleus from which it subsequently spreads through the cell. Actinomycin D could prevent this spread by preventing the completion of RNA molecules, which therefore do not dissociate from the DNA template.